An Adaptive Neuro-Fuzzy Inference Distributed Power Flow Controller (DPFC) In Multi-Machine Power Systems - Gurrala Madhusudhan Rao; V Anwesha Kuma; B.V. Sanker Ram (Institute of Advanced Engineering and Science, 2014)
The main theme of the paper which deals with the enhancing steady-state and dynamics performance of the power grids by Flexible AC Transmission System (FACTS) based on computational intelligence. The proposed technique will be applied to solve real problems in a power grid. The FACTS device, which will be used in the paper, is the most promising one, which known as the Distributed Power Flow Controller (DPFC). The paper achieves the optimization of the type, the location and the size of the power and control elements for DPFC to optimize the system performance. The paper derives the criteria to install the DPFC in an optimal location with optimal parameters and then designs an AI based damping controller for enhancing power system dynamic performance. In this paper, for every operating point genetic algorithm is used to search for controllers’ parameters, parameters found at certain operating point are different from those found at others. ANFISs are required in this case to recognize the appropriate parameters for each operating point.DOI: http://dx.doi.org/10.11591/ijpeds.v5i2.6311